2019
DOI: 10.1093/nar/gkz117
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MALAT1 releases epigenetic silencing of HIV-1 replication by displacing the polycomb repressive complex 2 from binding to the LTR promoter

Abstract: Long noncoding RNAs (lncRNAs) may either repress or activate HIV-1 replication and latency; however, specific mechanisms for their action are not always clear. In HIV-1 infected CD4 + T cells, we performed RNA-Sequencing (RNA-Seq) analysis and discovered an up-regulation of MALAT1 (metastasis-associated lung adenocarcinoma transcript 1), an lncRNA previously described in cancer cells that associate with cancer pathogenesis. Moreover, we found that MALAT1 promoted HIV-1 transcription and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
118
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 83 publications
0
118
0
Order By: Relevance
“…58 By associating with PRC2, MALAT1 detaches EZH2 bound to the HIV-1 LTR promoter, leading to the removal of H3K27me3 and reversal of epigenetic silencing of HIV-1 transcription. 59 lncRNAs from the antisense strand of p21 gene inhibit the transcription of p21 by inducing H3K27 methylation in its promoter region. 60 It has also been reported that altered expression of miRNAs and methylation of their promoters were correlated in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…58 By associating with PRC2, MALAT1 detaches EZH2 bound to the HIV-1 LTR promoter, leading to the removal of H3K27me3 and reversal of epigenetic silencing of HIV-1 transcription. 59 lncRNAs from the antisense strand of p21 gene inhibit the transcription of p21 by inducing H3K27 methylation in its promoter region. 60 It has also been reported that altered expression of miRNAs and methylation of their promoters were correlated in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, splicing alterations were not found after MALAT1 ablation in mice [37]. In contrast, alternative functions for MALAT1 were recently identified: MALAT1 could interact with the demethylated form of Chromobox homolog 4 (CBX4), also referred to as Polycomb 2 (Pc2), a component of the Polycomb Repressive Complex 1 (PRC1) [35,39,40]. This interaction controls the re-localization of growth control genes.…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of lncRNA NRON enhanced HIV-1 replication through increased activity of nuclear factor of activated T-cells (NFAT) and the viral long terminal repeat (LTR) [14]. Similarly, lncRNA MALAT1 releases epigenetic silencing of HIV-1 replication by displacing the polycomb repressive complex 2 from binding to the LTR promoter [15].…”
Section: Studying the Characteristics Of The Autoimmune Factors Of Ecmentioning
confidence: 99%